ANALISIS FAKTOR KEPUTUSAN JAMAAH UMROH MEMILIH PT. INTAN RAUDAH MADINAH (IRM) TOUR AND TRAVEL - Adiatma, Dani; Rukma, Deden Firman Syuyaman; Nurjihan, Nisrina (Fakultas Ekonomi Universitas Garut, 2023)
This study aims to find out what factors drive the decision of Umrah pilgrims to choose PT.Intan Raudah Madinah (IRM) Tour and Travel and the most dominant factor. The research method used in this research is exploratory factor analysis. Data collection techniques used are literature studies and field studies such as surveys, interviews and questionnaires. The population in this study were Umrah pilgrims who had already departed for IRM tour and travel in 2022. The sample used in this study was the purposive sampling method of 131 respondents. The data was tested using exploratory factor analysis with the help of IBM SPSS version 26. Based on the results of this study, the decision rate of Umrah pilgrims choosing PT. Intan Raudah Madinah (IRM) Tour and Travel is in the very high criteria. In factor analysis, of the 20 indicators determined after the correlation test was carried out, they were reduced to 18 indicators. After carrying out the factoring and rotation processes, 5 factors are formed correctly according to their correlation values, namely responsive and friendly factors, trust factors, service factors, responsibility factors, and safety and location factors. Of these 5 factors, the most dominating are responsive and friendly factors consisting of being responsive to needs, friendly, safe transportation, and affordable hotels.